Analyzing Cryptosystems by Using Artificial Intelligence - Ali, Faez Hassan; Al-Safi, Mohammed G S; Yousif, Ahmed Ayyoub (Al-Nahrain Journal of Science, 2018)
This paper aims to apply the Bees Algorithm for solving system of equations. The solving System of Equations may be linear or nonlinear for a number of unknowns. As an application of System of Equations, we can implement cryptanalysis attack algorithms on stream cipher systems using plaintext attack (or part from it). We consider the Geffe System (which has nonlinear combining function) to be our study case, which is depend on set of Linear Feedback Shift Registers, as a model of stream cipher systems, in the performance of Bees Algorithm by solving System of Equations for any number of variables of the output of Linear Feedback Shift Registers.The application divided into two stages, first, constructing System of Equations for the suggested cryptosystem, and the second, is attacking the variables of System of Equations which they are also represent the initial key values of the combined of Linear Feedback Shift Registers.